Association of the Quantity, Duration, and Type of Alcohol Consumption on the Development of Gouty Tophi. Issue 5 (14th December 2022) - Han, Lin; Li, Runze; Lu, Jie; Ren, Wei; Ning, Chunping; Pang, Jingyuan; Sun, Jian; Wang, Yao; Sun, Wenyan; Liu, Zhen; Wang, Can; Wang, Xuefeng; et al.
Abstract : Objective: To examine the association of alcohol consumption with the presence and development of ultrasound (US)–detected tophi and subcutaneous tophi in a Chinese gout population. Methods: A total of 554 patients with gout who underwent US and physical examination of the most frequently involved joints in gout were included in this study. Multivariable analysis was performed to assess the associations of the duration, quantity, and type of alcohol consumption with the presence, size, and number of US‐detected tophi and subcutaneous tophi. Results: Compared to non‐drinkers, excessive drinkers (>70 gm/week), long‐term drinkers (≥10 years), and spirits drinkers had a greater proportion, size, and number of US‐detected tophi and subcutaneous tophi (all P  < 0.05). After adjusting for confounders, excessive drinking (>70 gm/week) (odds ratio [OR] 1.79 [2.00 after adjustment]), long‐term alcohol consumption (≥10 years) (OR 1.96 [2.17 after adjustment]), and spirits consumption of (OR 1.81 [2.10 after adjustment]) were significantly associated with the presence of US‐detected tophi and subcutaneous tophi (all P  < 0.05), with the highest ORs among the identified risk factors. Among patients who already had US‐detected tophi or subcutaneous tophi, moderate drinking (≤70 gm/week) was associated with larger or multiple tophi (all P  < 0.05). Conclusion: Longer duration and higher quantity of alcohol consumption as well as spirits consumption are predictors for the development of US‐detected tophi and subcutaneous tophi in patients with gout. Among individuals who have US‐detected tophi and subcutaneous tophi, weekly alcohol consumption leads to the development of tophi regardless of amount consumed.